2003
DOI: 10.1126/science.1083247
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity in Free Niobium Clusters

Abstract: Electric deflections of gas-phase, cryogenically cooled, neutral niobium clusters [NbN; number of atoms (N) = 2 to 150, temperature (T) = 20to 300kelvin], measured in molecular beams, show that cold clusters may attain an anomalous component with very large electric dipole moments. In contrast, room-temperature measurements show normal metallic polarizabilities. Characteristic energies kBTG(N) [Boltzmann constant kB times a transition temperature TG(N)] are identified, below which the ferroelectric-like state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
119
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(124 citation statements)
references
References 16 publications
4
119
0
1
Order By: Relevance
“…Remarkably, very recently Moro et al reported detection of spontaneous electric dipole moments in Nb clusters [17] at low temperatures. Their observations that the effect is strongest for even number of electrons in the cluster and that it occurs only at low temperatures suggests that the effect is related to superconductivity [17] as proposed by the authors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, very recently Moro et al reported detection of spontaneous electric dipole moments in Nb clusters [17] at low temperatures. Their observations that the effect is strongest for even number of electrons in the cluster and that it occurs only at low temperatures suggests that the effect is related to superconductivity [17] as proposed by the authors.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, very recently Moro et al reported detection of spontaneous electric dipole moments in Nb clusters [17] at low temperatures. Their observations that the effect is strongest for even number of electrons in the cluster and that it occurs only at low temperatures suggests that the effect is related to superconductivity [17] as proposed by the authors. Moro et al concluded from their observations the existence of an internal electric field in the interior of the metal cluster of the order of 10 6 V /cm, and stress that such an internal electric field cannot occur in an ordinary metal and suggests a 'rigidity' of the electronic wavefunctions as well as a collective effect.…”
Section: Discussionmentioning
confidence: 99%
“…For Nb, by contrast, 0:5 represents a very strong dynamic screening effect. This anomalous behavior is currently under further investigation in our laboratory, but several indications of the unusual polarizability of Nb and its clusters have been documented in the literature [21,22].…”
mentioning
confidence: 99%
“…Furthermore, the present method to construct a size-defined cluster is widely applicable to various elements on several surfaces. Nanoclusters are known to exhibit unique physical and chemical properties that depend strongly on their size and constituent atoms [42][43][44][45][46] . This motivates us to create a variety of atomic-scale devices with different functionalities and to systematically embed them into desired nanoregions, which opens up novel nanofabrication to achieve atomic-scale integrated electronics for RT operation.…”
Section: Discussionmentioning
confidence: 99%